Ethical Considerations in Halal Pharmaceutical Industry: Insight from Islamic Teachings (Al-Aasar, 2025)
The incorporation of Islamic teachings into pharmaceutical research becomes a crucial and little-explored aspect as the pharmaceutical industry strives to bring its procedures into compliance with ethical and cultural standards. The purpose of this qualitative study is to shed light on the moral issues surrounding pharmaceutical research about Halal medicines through the lens of Islamic beliefs. Based on comprehensive interviews with academics, researchers, and religious leaders, the study aims to elucidate the complex ethical aspects associated with the creation and distribution of medications within Islamic contexts. The study will examine certain ethical problems that the sector faces, such as label transparency, compliance with Halal certification requirements, and fair distribution of Halal medications. The research aims to offer a comprehensive knowledge of how Islamic ethics may be effectively incorporated into industry decision-making processes through stakeholder engagement. Furthermore, the study seeks to understand how Islamic experts observe biotechnology developments, new technologies, and the moral implications they have for the halal pharmaceutical industry. This investigation aims to create the foundation for a sustainable and culturally aware Halal pharmaceutical sector by identifying problems and offering solutions. This study provides a distinctive viewpoint based on Islamic beliefs to the continuing conversation about ethical issues in the pharmaceutical industry. To guarantee that the Halal pharmaceutical sector upholds the greatest standards of morality and integrity, it seeks to promote the thoughtful fusion of Islamic ethical principles with international pharmaceutical practices.